SLANG, IDENTITY, AND DIGITAL INTERACTION IN K-POP FAN COMMUNITIES ON INSTAGRAM AND TIKTOK - Anindita, Widyashanti; Dewanti, Sekar Ayu (PT Akselerasi Karya Mandiri, 2025)
This study explores the use of slang within the K-Pop community on the social media accounts of @soohyunk216 on Instagram and TikTok. Employing a descriptive qualitative method, the researchers analyzed 63 data points of slang expressions collected from comments between September and October 2024. The study classifies slang usage based on Bloomfield’s (1933) four forms of slang; abbreviations, funny mispronunciations, shortened forms, as well as interjections and examines their social functions through Eble’s (2006) framework. Findings reveal that slang is predominantly used to shorten writing, express communal support and identity, convey humor, and implement euphemized or sarcastic language including hate speech. This research confirms the dynamic role of slang in digital fan communities, reflecting both linguistic creativity and social bonding. The results contribute to sociolinguistic understanding of online language variation and offer valuable insights for intercultural communication and translation studies involving multilingual digital communities.